Analysis of a Chinese Pedigree With Familial Chylomicronemia Syndrome Reveals Two Novel LPL Mutations by Whole-Exome Sequencing - Liu, Ying; Lan, Zhangzhang; Zhao, Fang; Zhang, Shuangchuan; Zhang, Wenyong (Frontiers in Genetics, 2020)
Familial chylomicronemia syndrome (FCS) is a rare monogenic autosomal recessive disease caused by loss-of-function mutations in genes involved in chylomicron break down through hydrolysis of triglycerides into free fatty acids. Patients are often diagnosed in early childhood with extremely high triglyceride levels and symptoms including abdominal pain, eruptive cutaneous xanthomata, hepatosplenomegaly and significant cognitive, psychological and social impairment. Most serious medical condition suffered by FCS patients are recurrent acute pancreatitis. Lipoprotein lipase (LPL) gene mutation accounts for majority of the known pathogenic mutations. Early diagnosis and strict low-fat diet is critical for successful management of the triglyceride concentration to lower the risk of pancreatitis. The true prevalence of FCS in China is unknown and here we report a Chinese female preterm neonate presented with extremely high triglyceride level of 22.11 mmol/L on day 13 after birth. Clinical and laboratory workup including whole-exome sequencing revealed two novel compound-heterozygous LPL mutations (c.406G>C and c.829G>C) that are co-segregated with her nonconsanguineous parents, consistent with autosomal recessive inheritance. A diagnosis of FCS based on clinical, biochemical and genetic ground was made to guide her management.